Immune response of DNA vaccinated-gilthead seabream (Sparus aurata) against LCDV-Sa infection: relevance of the inflammatory process - Leiva-Rebollo, Rocio; Gémez-Mata, Juan; Castro, Dolores; Borrego, Juan J.; Labella, Alejandro M. (Frontiers in Immunology, 2023)
Lymphocystis disease is one of the main viral pathologies affecting cultured gilthead seabream (Sparus aurata) in the Mediterranean area. Recently, we have developed a DNA-vaccine based on the major capsid protein (MCP) of the Lymphocystis disease virus 3 (LCDV-Sa). The immune response triggered by either LCDV-Sa infection or vaccination have been previously studied and seems to be highly related to the modulation of the inflammatory and the IFN response. However, a comprehensive evaluation of immune-related gene expression in vaccinated fish after viral infection to identify immunogenes involved in the vaccine-induced protection have not been carried out, and it is the aim of the present study. To fulfil this objective, samples of head-kidney, spleen, intestine and caudal fin from fish were analysed using an OpenArray® platform containing targets related to the immune response of gilthead seabream. The results obtained showed an increase of deregulated genes in the haematopoietic organs between vaccinated and non-vaccinated fish. However, in the intestine and fin, the results showed the opposite trend. The global effect of fish vaccination was a significant decrease (p<0.05) of viral replication in groups of fish previously vaccinated, and the expression of the following immune genes related to viral recognition (tlr9), humoral and cellular response (rag1 and cd48), inflammation (csf1r, elam, il1β, and il6), antiviral response (isg15, mx1, mx2, mx3), cell-mediated cytotoxicity (nccrp1), and apoptosis (prf1). This exclusive modulation of the immune response provoked by the vaccination seems to control the progression of the infection in the experimentally challenged gilthead seabream.